Relationship between the occlusal vertical dimension and anthropometric measurements of the fingers. - Yuri Castro-Rodríguez; Kamila Sihuay-Torres (Universidad de Concepción., 2019)
The alteration of the vertical dimension can deteriorate the facial harmony, and it can be measured through objective and subjective methods, although many of which are not reliable. Objective: Relate the anthropometric fingers length with the measurement of the vertical occlusal dimension (VOD). Material and Methods: Cross-sectional, observational study that included 114 students from the School of Dentistry with class I malocclusion and complete dentition. The VOD was evaluated as the measurement between the subnasal points and the mental point; anthropometric measures included the length of the fingers (from the most mesial fold to the most distal edge) and the distance projected between the thumb and the index finger. Results: The average VOD was 64.03±5.15mm. A correlation was found between the VOD and the index finger length (p<0.01, r=0.29), between the VOD and middle finger length (p<0.01, r=0.31) and correlation between the VOD and the length of the little finger (p<0.05, r=0.23). No correlation was found between the VOD and the ring finger lengths (p= 0.051) or thumb (p=0.12). Conclusions: The anthropometric measurements of the index finger, middle finger, little finger and the projection of the thumb on the index finger correlated with the length of the vertical occlusal dimension.